Redescription of adults of Simulium jeteri (Py-Daniel, Darwich, Mardini, Strieder & Coscarón, 2005) (Diptera: Simuliidae) - Nascimento, Jeane M. C. Do; Hamada, Neusa; Pepinelli, Mateus; Mardini, Lúcia B. L. F. (Zootaxa, 2019)
Simulium jeteri (Py-Daniel, Darwich, Mardini, Strieder & Coscarón, 2005) was not fully described, because only pharate male and female adults extracted from pupae were used for the original descriptions. Important diagnostic characters were either incompletely or poorly described. During field work in areas at the same hydrographic basin of the type-locality, we were able to rear adult stages. The main objective of this study is to redescribe the male and female of S. jeteri, providing a complete description, including morphological characteristics not reported before, such as, presence of a median ventral projection on male ventral plate and a bilobed anal lobe on female terminalia. Additional characters of pupae and larvae are given. The addition of new characters will be useful to better understand phylogenetic relationships among species in this group. Females of S. jeteri are not known to bite.